Optimization of Degree of Polarization of Photoluminescence Measurements Using Digital Signal Processing - Lascos, Steven (My University, 2007)
The experimental technique of measuring the degree of polarization of photoluminescence is studied. Digital signal processing techniques are applied to characterize the spectrum of the experiment and optimize its configuration for accuracy and precision. Digital phase sensitive detection is analyzed and the design of a digital lock-in amplifier is presented. Mechanical frequency modulation of the photoluminescence is reported and a physical model is presented. Procedures for enhancing measurements are stated with a reduction in noise levels of approximately 50% reported.
Keywords: Optimization; Polarization; Photoluminescence; Digital Signal Processing